Impact of occupation on respiratory disease - Nathell, L.; Malmberg, Per; Lundbäck, Bo; Nygren, Å (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'This study identified occupations with a marked impact on sick leaves due to respiratory disease. ' ' METHODS ': 'A national sick-leave register containing information on all sick leaves exceeding 14 days, physicians` diagnoses, and the occupational status of all manual and service employees in the private sector in Sweden was studied. Sick-leaves during 1992-1994 (N=210 755) were analyzed with special attention to respiratory disease and occupation. ' ' RESULTS ': 'Respiratory disease accounted for 4.4% of the total number of sick leaves. The incidence of long-term (≥90 days) sick leaves due to respiratory disease was 3 times higher in occupations with a high incidence than in those with a low incidence. There was a high correlation (r=0.80) between the incidence of long-term sick leave due to respiratory disease and sick leave due to all other conditions; this finding suggests that market and selection factors may play an important role in determining the overall risk for sick leave in various occupations. The proportion of sick leaves due to long-term respiratory disease out of all long-term disease was compared between occupations. Agricultural workers had a 46% higher proportion of long-term respiratory disease than metal workers. Industrial workers, food industry workers, and painters were also occupations with an increased risk. These findings could not be explained by differences in age or smoking habits. ' ' CONCLUSIONS ': 'Major differences were found among manual and service occupations regarding long-term sick leave due to respiratory disease. Several occupations, in which exposure to respiratory sensitizers and irritants are known to occur, were among those in which workers had an increased risk for long-term respiratory disease.
Keywords: agriculture; food industry; health economics; long-term sick leave; metal worker; occupational asthma; painter; secondary prevention; sick leave